Bone bruises in anterior cruciate ligament injured knee and long-term outcomes. A review of the evidence - Papalia R; Torre G; Vasta S; Zampogna B; Pedersen DR; Denaro V; Amendola A (Dove Medical Press, 2015)
Rocco Papalia,1 Guglielmo Torre,1 Sebastiano Vasta,1 Biagio Zampogna,1 Douglas R Pedersen,2,3 Vincenzo Denaro,1 Annunziato Amendola3 1Department of Orthopaedic and Trauma Surgery, Campus Bio-Medico University of Rome, Rome, Italy; 2Department of Biomedical Engineering, 3Department of Orthopaedics and Rehabilitation, University of Iowa, Iowa City, IA, USA Background: Bone bruises are frequently associated with anterior cruciate ligament (ACL) tears as a result of trauma or direct shear stress of the bone. Purpose: To review the evidence regarding the characteristics of the bone bruise associated with ACL tears, its relevance on clinical outcomes, and its progression over time. In particular, the long-term effects of the bone bruise on the knee osteochondral architecture and joint function were evaluated. Study design: Review; level of evidence: 4. Methods: An electronic search was performed on PubMed. Combinations of keywords included: “bone bruise AND knee”; “bone bruise AND anterior cruciate ligament”; “bone bruise AND osteo-chondral defects”. Any level of evidence studies concerning bone bruises in patients with partial or complete ACL tears were retrieved. Results: A total of 25 studies were included; three of them investigated biomechanical parameters, seven were concerned with clinical outcomes, and 15 were radiological studies. Evaluation of the bone bruise is best performed using a fat-saturated T2-weighted fast spin echo exam or a short tau inversion recovery sequence where fat saturation is challenging. The location of the injury has been demonstrated to be more frequent in the lateral compartment of the joint (lateral femoral condyle and lateral tibial plateau). It is associated with ACL tears in approximately 70% of cases, often with collateral ligament or meniscal tears. Mid- and long-term outcomes demonstrated a complete healing of the marrow lesions at magnetic ρresonance imaging, but chondral defects detected with T1ρ sequences are still present 1 year after the ACL injury. Functional examination of the knee, through clinical International Knee Documentation Committee scores, did not show any correlation with the bone bruise. Conclusion: Although bone bruise presence yields to higher pain levels, no correlation with functional outcomes was reported. Most studies have a short-term follow-up (<2 years) compared to the length of time it takes to develop post-traumatic osteoarthritis, so it still remains unclear whether the initial joint injury and bone bruise have a direct relationship to long-term function. Keywords: bone bruise, anterior cruciate ligament, magnetic resonance imaging, knee